FEATURES, DISTINCTIVE ASPECTS AND TRENDS OF GLOBALIZATION: THE NEXT GLOBAL STAGE - Flores Konja, Adrián Alejandro (2011)
The phenomenon of globalization, complex and changing, has greatly impacted in all areas, no doubt, but conceptual understanding is made difficult by its very nature. Among the most outstanding efforts and recognized its conceptual approach highlights the Kenichi Ohmae, who has summarized the characteristics, distinctive characteristics and trends of globalization on political and economic aspects. In this preliminary report describes an exploratory investigation of patterns and trends identified by Ohmae, and compared with the observations of researchers on the global and national reality in this reality by projecting the trends presented by Ohmae. Ohmae Indicates that the main protagonists in the global scene have changed, with the disappearance or “reinvention” of national states, and the emergence “States region.” also reduced state intervention in economic decisions, this also being a hallmark of globalization in economics, said the three most important features of the global economy, which are to be boundless, to be invisible and earnings multiply. According to Ohmae, the platforms of globalization are: the English language, the Windows operating system, the U.S. dollar and trademarks, and, secondly, the new corporate culture, ATM networks and electronic transactions. Emphasis on the “cibercontinente” as the new “place” of the economy, instead physical economy. Made by trends in economic Ohmae 2005 have been denied by the reality of the American financial crisis of 2008, and its challenge to the dollar system, and factors Ohmae aside, such as geopolitics and drug trafficking, but also the emergence of national statescontinent nations such as China, India and Russia are gaining strength in some cases for and others against the grain of the trends identified.